Prognostic and clinicopathological implications of expression of Beclin-1 and hypoxia-inducible factor 1α in serous ovarian carcinoma: an immunohistochemical study - Alabiad, Mohamed; Harb, Ola; Mandour, Doaa; Hemeda, Rehab; Z. Ahmed, Rham; El-Taher, Ahmed; Osman, Gamal; Shalaby, Amany; A.A. Alnemr, Amr; T. Abdelfattah, Mostafa (Polish Journal of Pathology, 2021)
Serous ovarian carcinoma (SOC) is an ovarian cancer with a high fatality rate. Therefore, a lot of researchers have tried to identify novel prognostic biomarkers which might improve the patient prognosis. The aims of the study were to detect the tissue protein expression of Beclin-1 in addition to HIF-1α in SOC patients, to evaluate the relationship between their expression, the clinicopathological parameters, patients’ prognosis, and the relation to chemotherapy resistance in SOC. We evaluated the expression of Beclin-1 in addition to HIF-1α in 60 patients with SOC using immunohistochemistry, followed all patients for about 36 months, analyzed associations between both markers' expression, clinicopathological data, and patients’ prognosis. Beclin-1 expression was related to low grade (p = 0.002), early SOC stage, absence of peritoneal spread (p = 0.006), and absence of lymph nodes, and distant metastases (p = 0.004 and < 0.001 respectively), while HIF-1α expression was associated with higher grade and stage (p = 0.007), and presence of nodal and distant metastases (p < 0.001 and = 0.012 respectively). High Beclin-1 expression and low HIF-1α expression were positively associated with good response to chemotherapy (p = 0.047 and p = 0.022 respectively), a lower recurrence rate after successful therapy (p = 0.006 and < 0.001 respectively), and increased three-year recurrence-free and overall survival rates (p < 0.001). In SOC patients; Beclin-1 is a good prognostic marker, while HIF-1α is a poor prognostic marker.